CARP SPAWN POTENTIALITY OF PALEZAGHAT (BIHAR) - Prasad, R R (Indian Journal of Fisheries, 2011)
Some observations on the assemibly of fish spawn at Palezaghat during the years 1974 and 1975 are presented. The spawn wihich is collected in the vascinity of the assembly centre, arrive in the evening and sold to fish farmers. The Quantity of spawn disposed off from this centre constitute only 7% of the total spawn produced in Bihsr. Private entrepreneurs are taking more interest in spawn trade than Government agency; The annual turn over of this centre has also been presented.